NEOLOGISMS IN VIRTUAL DISCOURSE, THEIR STRUCTURAL AND SEMANTIC CHARACTERISTICS - DYACHUK, Tetyana; LYTVYNSKA, Svitlana (Linguistic and Conceptual Worldviews, 2024)
Ваckground. The relevance of the study of neological lexicon is determined by the need to constantly organize the formal level of the lexical-semantic system of the language.Methods. Factual material was selected using a continuous sampling method from various sources (see list of sources used). The descriptive method was used to study the features of communication in the virtual environment, the induction method was used to generalize and draw conclusions, and the method of structural analysis was used to identify ways of creating new vocabulary.Results. The article analyzes neologisms selected from online media from the point of view of structure, semantics, and origin. Neolexems were found to be multi-structured (words, juxtapositions, especially many abbreviations, word combinations). From the point of view of origin, borrowings from the English source language continue to dominate. Neolexes of Ukrainian origin are extremely few. The process of expanding the semantic structure of some commonly used words continues.Conclusions. Online media is an important source of formation and functioning of neolexes. The prospect of neologism research is obvious. The problem of adequate replacement of neologisms of foreign origin with Ukrainian equivalents, development of effective mechanisms of "promotion" of Ukrainian names from the sphere of fixation to the sphere of functioning is particularly relevant.
Keywords: neologism, sphere of fixation, sphere of functioning, foreign word, borrow-ing, semantic structure of the word